KAPASITAS PEMERINTAH DESA DERMAJI KABUPATEN BANYUMAS DALAM PENGURANGAN RISIKO BENCANA - Diar Budi Utama; Hendrawan Bayu Prewito; Hendro Pratikno; Yanuar Udianto Kurniadi; Hayatul Khairul Rahmat (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The capacity of the village government is demanded to be able to respond to public needs in one sector, namely disaster. Where a disaster is a condition of events that are beyond human ability that causes loss of life and property. So this requires a quick response attitude from stakeholders as an effort to joint obligations, one of which is the important role of the village government. The number of landslide disasters in each sub-district in Banyumas Regency in 2014-2016, Lumbir District, was the most frequent occurrence of 20 times. Dermaji Village is the village most frequently hit by landslides in Lumbir District, recorded 8 times from 2014-2016. The importance of research on the capacity of the Village Government in efforts to reduce disaster risk, the purpose of this study is to analyze the capacity of the Village Government of Dermaji, Banyumas Regency in disaster risk reduction. The research method used is a qualitative method to obtain accurate information from competent informants. The results of the study show that the Dermaji Village Government has not yet established a disaster management regulation as a mitigation effort, so it is necessary to formulate a disaster risk reduction policy formulation at the village level with the support and awareness of the community as an effort of legitimacy and legality.